PREVALENSI DAN GAMBARAN GANGGUAN TIDUR BERDASARKAN KARAKTERISTIK MAHASISWA SEMESTER I PROGRAM STUDI PENDIDIKAN DOKTER FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA TAHUN 2015 - Gunanthi, Ni Made Widi Widi Mas; Diniari, Ni Ketut Sri (E-Jurnal Medika Udayana, 2016)
THE PREVALENCE AND DESCRIPTON OF SLEEPING DISTURBANCE BASED ON CHARACTERISTIC OF THE MEDICAL STUDENT ON THE FIRST SEMESTER AT UDAYANA UNIVERSITY 2015 Background: Sleep disorder is a regular problem suffered by students, especially medical student. There is no research regarding sleep disorder in Medical Student in Udayana University in the beginning of the lectures. Method: This research used descriptive quantitative cross sectional method. The Questioners used in this research consist of the respondent characteristic questioner and sleep disorder questioner St. Mary’s Hospital (SMH) which has been adopted. Result and Discussion: The result of the research found 32 respondent have sleep disorder (45,7%), the inclination of sleep disorder based on the characteristic respondent found that the 20 years old students have 100% sleep disorder, female students (66,7%), renting room students (52,3%) and the students who join the organization activity (47,5%). From 32 students who have sleep disorder, there are 31,2 % wake up once to twice when they are sleeping. There 34% of them sleep for 5 hours. There 56,2 % of the student have insomnia from medium level to high level. There are 50% of them still feel sleepy after waking up. Conclusion: The number of sleep disorder in the respondent shows that less amount than other research had been done however the amount still higher on the average population both teenager and adult. Sleep deprivation affected their academic perfomance.
Keywords: Sleep disturbance, medical student, St. Mary’s Hospital (SMH)